Sensemaking in State-Owned Enterprises: The Case of "Russian Post" - Konobeeva, Elena (Journal of Economic Sociology, 2015)
2013–2014 was a stage of organizational transformation of the Russian postalsystem, which caused disruption of the organizational structure and doublingof its operational elements. This article begins by exploring the resultingsituation of ambiguity and uncertainty caused by this disruption. Under theseconditions, according to K. Weick, the sensemaking process should play anessential role in organizational performance. This research project aims to identify the structural features of the Russian postal system during the reorganization stage, as well as at defining the meanings which employees gave to ongoing changes. The data was collected through participant observation from the position of Moscow Central Office postal employee from June 2013 to September 2014; fourteen interviews of employees and document analysis were conducted as well. Information was recorded in field notes and diary and analyzed with open and axial coding according to the procedures of grounded theory. The main findings presented in this article are the disruption of structure and the following complexities in its functional performance and the coexistence of two organizational images between more experienced workers affected by organizational change and the newcomer employees with brand new ideas. Employees’ perception of the Russian postal system is presented as simultaneously government and commercial, profitable and detrimental, typical and specific organization. These dual images can cause difficulties both in employees’ communication and organizational performance.